WATER TREATMENT USING NATURAL COAGULANT: A REVIEW ON THE POTENTIAL UTILISATION OF BANANA WASTE - Azamzam, Abdassalam A.; Alabdi, Abdalahafid J.; Yahya, Esam Bashir; Lalung, Japareng; Ahmad, Mardiana Idayu (Malaysian Journal of Science, 2024)
The massive industrial and agricultural development in the past few years has increased the pollution level of water bodies. Several studies have concluded that the global depletion of freshwater resources will result in difficulties accessing clean water. Plant-based water treatment techniques have attracted great interest in the past few years due to their safety and cost-effectiveness compared with chemical-based techniques. Natural coagulants have been extensively studied in terms of the type of plant and the mechanism of coagulation. Banana is one of the most famous tropical fruits from the Musa genus in the Musaceae family. It is widely consumed in Malaysia, especially Musa acuminata, Musa balbisiana, and Musa paradisiaca, resulting in tremendous amounts of biomass residue, including peels, stems, and leaves, with high potential use for wastewater treatment applications. This review aims to highlight the advantages of natural coagulants and to discuss the potential use of different banana wastes in water treatment applications.